Análisis socio-jurídico del sistema de responsabilidad penal juvenil (2005)
This article will analize the socio-juridical bases and consequences to the systems of juvenile penal responsibility which turns greatly important in Colombia, for the urgency to modify such a system has been in discussion since a while back. The lack to specialized literature has brought forth all types of judgments into various directions which has left nothing good as far as juvenile responsibility is concerned, in a country where the situation of delinquency amongst minors is becoming a more than a grave issue. Thus, before the disjunction expounded in front of us between a repressive juvenile penal system and impunity the re-searcher should thoroughly study the philosophical and sociological suppositions in order to propose other real and concrete alternatives tor a reform especially focused upon the understanding of what relates to a juvenile I which implies a dialogue amongst knowledges!, of the representation - a function in the world of the true daily juridical penal system, and of the judge figure in such processes, among other elements. Therefore, this article will carry out a profound study of the socio-juridical elements that are considered to be most relevant to function as a theoretical basis for the process of the reform to the system of juvenile responsibility